The Governance of the Colombian Health System from the Stakeholders’ Perspective - Restrepo-Zea, Jairo Humberto; Zapata-Cortés, Olga Lucía (Revista del CLAD Reforma y Democracia, 2022)
Although health governance can bring benefits, such as higher public spending, control of corruption, higher levels of participation and better management, there is no unified notion of the term or the associated processes. The aim of this research is to understand the actors’ perspective on the governance of the Colombian health system. To this end, a qualitative study is carried out, based on the application of a survey with structured and open questions to 141 leaders of the health system, under a non-probabilistic convenience sampling. The analysis shows a low knowledge of the term governance. Governance is rated at a low level (2.5/5.0), as are its key functions (2.6); with citizen participation, transparency and accountability being the worst rated. In addition, there knowledge of the Coordination and Advisory Body and the Intersectoral Commission on Public Health is lacking, and the contribution of both to the system’s objectives is considered low. Most of the participants pointed out corruption as the main problem of the system (72%), in addition to the articulation of actors (41%) and lack of financing (30%). Among the strengths and opportunities, the regulatory framework and the Statutory Health Law stand out. It is concluded that, despite the achievements, the health system has difficulties and situations to be solve, such as corruption, showing weak governance. The lack of appropriate and effective bodies or spaces for discussion, coordination and decision-making is notorious, in order to guarantee the right to health.
Keywords: Governance; Health System; Health Administration; Health Services; Citizen Participation; Cooperation; Surveys; Colombia